Alexitimia y ansiedad social en estudiantes de primer año de la Facultad de Salud Humana de la Universidad Nacional de Loja - Cevallos Yaguana, Kelly Dayana (2023)
Alexithymia and social anxiety are commonly found psychological problems in the general population. Both phenomena cause a significant impact on people's lives who experience them, especially among young people, such as university students. In this context, the present research aimed to determine the relationship between alexithymia and social anxiety in first-year students of the Human Health Faculty at Universidad Nacional de Loja and to measure different levels of these two variables. This research was based on a quantitative approach, with a non-experimental, cross-sectional, and correlational design. Two psychometric instruments, the Toronto Alexithymia Scale agreed upon for Latin America and the Liebowitz Social Anxiety Scale, were used to assess 167 university students selected by non-probabilistic convenience sampling and selection criteria, whose ages ranged from 17 to 23 years. The results of the research indicate a positive and significant correlation between alexithymia and social anxiety. Furthermore, a large majority of the students (68.9%) were found to have alexithymia, while a significant number showed moderate (35.3%) or severe (23.4%) levels of social anxiety. The average score for alexithymia was 60.42 and for social anxiety, it was 58.74. The results suggest that the higher level of alexithymia, the higher the level of social anxiety. Moreover, it was observed that the prevalence of these two variables is stronger in the female gender. Finally, based on the obtained results, a group intervention plan was developed to tackle both problems